Causal relationship between genetically predicted type 2 diabetes mellitus and male infertility - Fan, Cuihua; Zhang, Jiandong; Qiu, Dongbiao (Frontiers in Endocrinology, 2024)
Diabetes mellitus (DM) stands as the most prevalent endocrine abnormality affecting the physiological systems and organs and impairing the male reproductive functions. Type 2 Diabetes Mellitus (T2DM), accounting for about 90-95% of DM, is closely associated with male infertility. However, the magnitude of the causal relationships between T2DM and male infertility remains unclear. The current investigation was to explore the causal relationship between T2DM and male infertility utilizing the Mendelian Randomization (MR) analysis. A two-sample MR (2SMR) analysis was conducted to investigate the causal relationship between T2DM and male infertility in the European population from the genome-wide association study (GWAS) summary data that was publicly accessible. GWAS for T2DM and male infertility were extracted from the IEU Open GWAS Project database, with the resulting data encompassing 680 cases and 72,799 controls as the outcome data. Five MR methods were employed for the 2SMR analyses, namely the MR-Egger, weighted median estimation (WME), weighted mode (WM), inverse-variance weighted (IVW), and simple mode. The primary analytical technique utilized in this study was the IVW method, and a multivariate MR analysis was executed to examine the potential mediating influences of T2DM on male infertility. Following were the odds ratios (ORs) and associated 95% CIs derived from IVW (fixed effects), MR-Egger, WM, WME, and simple mode approaches: 0.824 (95% CI 0.703-0.966), 0.726 (95% CI 0.527-1.001), 0.827 (95% CI 0.596-1.150), 0.841 (95% CI 0.654-1.082), and 0.875 (95% CI 0.544-1.405), respectively. The outcomes of the heterogeneity tests were P=0.378 and P=0.384, respectively, implying no heterogeneity. Egger-intercept outcomes were P=0.374, highlighting the absence of pleiotropy. The stability of the results was affirmed through the leave-one-out analysis. Notably, all F-values surpassed 10, indicating the absence of weak bias attributed to instrument variables(IVs). This research furnishes evidence supporting a causal association between T2DM and male infertility. These insights offer a foundation for future investigations aiming to establish the association between genetically predicted T2DM and male infertility. These outcomes suggest the significance of active monitoring and proactive measures for preventing infertility in male individuals with T2DM. Furthermore, careful consideration is required for individuals of reproductive age to prevent and treat T2DM.